A liderança feminina nos hemocentros e sua relação com a melhoria da qualidade - Neira, Adarlette (2009)
This study aims to identify the existence of the relationship between the performance of female leadership and recognition obtained by Brazilian blood banks in the evaluation of institutional performance in cycles of the National Public Management, the PQGF The relevance of this study referred to the innovative initiative to include various aspects of organizational studies, in other words, leadership, feminism and public management, directed to health and particularly the Brazilian blood center coordinators. The present dissertation it is a design study of multiple cases in order to provide similar results and/ or contrasting reasons predictable, according to the sample considered, the views expressed by leaders of Brazilian blood center coordinators in the questionnaires applied. The leaders of the participating blood centers are women, presenting a larger number of women as subordinates and functional body of the researched institution. The respondents, whose blood centers participated in the PQGF and obtained recognition of their performance, were unanimous in confirming the organizational changes arising from the adoption of the model excellence in governance and the awards process.